A105 AN ONLINE EDUCATIONAL PORTAL IMPROVES CONCERNS OF INFLAMMATORY BOWEL DISEASE PATIENTS REGARDING PREGNANCY AND MEDICATION. (1st March 2018) - Sutton, R T; Wierstra, K; Ambrosio, L; Dieleman, L A; Halloran, B P; Kroeker, K I; Fedorak, R; Wong, K; Berga, K; Huang, V
Abstract: Background: The impact of a mother's chronic disease on fetal development makes dealing with inflammatory bowel disease (IBD) during pregnancy complicated. Almost 50% of women with IBD have poor reproductive knowledge; this has been associated with unsubstantiated concerns toward pregnancy, and towards IBD medications. With the help of Pixel Designs Company, we developed an educational web portal to address these concerns. Aims: To evaluate the educational web portal for effectiveness at improving pregnancy and medication concerns in IBD patients. Methods: IBD patients aged 18–45 years were invited to participate in a study to evaluate the effectiveness of an educational web portal covering the topics of heritability, fertility, surgery, pregnancy outcomes, delivery, postpartum, and breastfeeding in the context of IBD and IBD medications. Patients completed pre- and post-study questionnaires about seven IBD-specific pregnancy concerns, and identified Likert scores for nine medication concerns from the Beliefs About Medicines Questionnaire (BMQ).The non-parametric McNemar's test was used to determine if the proportion of patients who had each pregnancy concern decreased post-intervention. For medication concerns, the Wilcoxon signed-rank test was used to compare median differences between Likert scores. 95% confidence intervals and SPSS Version 23 were used for all analysis. Results: Seventy-eight of 111 patients (70.3%) completed pre and post-study questionnaires. Demographics for the 78 are as follows: median age 29.3 (IQR 25.6 - 32.9) years; 54 (69.2%) Crohn's disease; 21 (26.9%) ulcerative colitis; 63 (80.3%) females, 5 (7.9%) currently pregnant and 19 (30.2%) previously pregnant. Medication history: 10 (12.8%) sulfasalazine, 67 (85.9%) mesalamine/5-ASAs, 17 (21.8%) budesonide, 63 (80.8%) steroids, 12 (15.4%) methotrexate, 55 (70.5%) azathioprine/mercaptopurine, 42 (53.8%) biologics, and 38 (48.7%) antibiotics. The intervention significantly decreased the proportion of patients who reported reproductive concerns regarding: fertility, added stress of raising a child affecting IBD, birth defects from IBD, pregnancy causing a flare-up, and inability to breastfeed due to IBD or medications. The BMQ Likert scores significantly decreased post intervention for concerns about having to take IBD medication, becoming too dependent on IBD medication, and the long-term effects of IBD medication. Conclusions: The educational web portal effectively reduced the proportion of patients who reported certain concerns about pregnancy in IBD, in addition to concerns regarding their IBD medications. Funding Agencies: AIHS